Genetic characterization of porcine parainfluenza virus 1 (PPIV-1) in pig farms: first report of PPIV-1 in Thailand and Myanmar - Phyu, Hnin Wai; Charoenkul, Kamonpan; Nasamran, Chanakarn; Udom, Kitikhun; Phyu, Eaint Min; Thaw, Yu Nandi; Soe, Han Win; Chaiyawong, Supassama; Lin, Thant Nyi; Maw, Min Thein; Amonsin, Alongkorn (Frontiers in Veterinary Science, 2025)
Porcine parainfluenza virus 1 (PPIV-1) is a paramyxovirus causing respiratory infections in pigs and has been reported worldwide. In this study, we conducted a cross-sectional survey of PPIV-1 in pig farms in Thailand and Myanmar from January 2022 to December 2023. Nasal swab samples from pigs in Thailand (n = 1,042) and Myanmar (n = 449) were collected from clinically healthy pigs and pigs with respiratory signs. PPIV-1 detection was carried out using the L gene-specific RT-PCR assay. Our results showed that 3.65% (38/1042) and 7.57% (34/449) were positive for PPIV-1 in Thailand and Myanmar, respectively. The viruses (n = 15) were subjected to whole genome sequencing (n = 4) and F and HN gene sequencing (n = 11). Genetic and phylogenetic analyses showed that Thai PPIV-1 (n = 7) was grouped into PPIV-1 lineage II (American lineage) and closely related to American and Chinese strains. On the other hand, one Thai PPIV-1 strain (n = 1) and Myanmar PPIV-1 (n = 7) belonged to lineage I (European lineage) and was closely related to European, Hong Kong (China), and South Korean strains. Our findings suggest that PPIV-1s from both lineages (I and II) are circulating in pigs in Thailand, and PPIV-1 of lineage I is circulating in pigs in Myanmar, suggesting high genetic diversity of PPIV-1 in the Southeast Asia region. This study is the first to report whole-genome sequences of PPIV-1 from pigs in Thailand and Myanmar. Our result provided insights and information about the current disease status and genetic diversity of PPIV-1 in pig farms, which will benefit further animal disease surveillance, prevention, and control.